APLIKASI KLASIFIKASI STATUS GIZI BALITA MENGGUNAKAN METODE NAÃVE BAYES BERBASIS ANDROID - Darnila, Eva; Maryana, Maryana; Azmi, Muhammad (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2021)
Malnutrition is a condition that a person experience because the lack of nutrient intake or the amount of nutrients that exist is still below standard. nutritional problems are most commonly experienced by toddlers. Nutritional status in toddlers is a benchmark of the health condition of toddlers. The nutritional status of toddlers can currently be measured based on anthropometric index using WHO standards. Anthropometrics is an assessment of the nutritional status of toddlers determined through measurements of the human body In this study measurement of nutritional status using a technique in data mining namely NaÃ¯ve Bayes Method that aims to facilitate health centers in measuring the nutritional status of toddlers quickly through android-based applications. NaÃ¯ve Bayes method performs nutritional status classification of toddlers that will produce a classification very thin, thin, normal and fat. Based on data taken from banda sakti health center Lhokseumawe city which then carried out the classification process, obtained the results of nutritional status "skinny" with data testing male sex, weight 7.4 kg and height 64.6.